Integration of metabolomics and transcriptomics analyses reveals the effects of nano-selenium on pak choi - Yanyan Wang; Peiheng Sun; Mingying Nie; Jianyun Zhan; Liu Huang; Junda Wu; Jie Zhang; Xiaowu He; Na Li; Longsong Hu; Shiyu Liu; Chengfu Yuan; et al. (Scientific Reports)
Abstract Selenium is an indispensable nutrient for plants, and optimizing selenium levels can enhance plant growth and metabolism, leading to improved yield and quality. In comparison to conventional inorganic or organic selenium fertilizers, nano-selenium demonstrates superior safety and enhanced biological activity, making it more suitable for crop production. Although nano-selenium fertilizer is extensively used in various crops, its application in pak choi remains limited. As a vital source of selenium, previous research on pak choi (Brassica chinensis var. pekinensis cv. 'Suzhouqing') has primarily focused on investigating physiological effects with limited exploration of the molecular mechanism. Therefore, this study aims to investigate the impact of nano-selenium on pak choi through an integrated analysis of transcriptome and metabolome. Specifically, we examined the effects of different concentrations of nano-selenium (0, 5, 10 and 20 mg L−1) on the growth and nutritional quality of Suzhouqing. The findings revealed that a low concentration (5 mg L−1) of nano-selenium significantly increased leaf weight and total selenium content, while modulating primary metabolites such as soluble amino acids, proteins, sugars and ascorbic acid. Additionally, it influenced secondary metabolites including glucosinolates, phenolic acids and flavonoids. Consequently, this enhancement in growth performance and nutritional quality was attributed to the regulation of pathways involved in selenocompound metabolism, phenylpropanoid biosynthesis, and flavonoid biosynthesis by key enzymes such as methionine S-methyltransferase, 5-methyltetrahydrofolate-homocysteine methyltransferase, kynurenine-oxoglutarate transaminase, thioredoxin reductase, phenylalanine ammonian-lyase, 4-coumarate-CoA ligase, flavonoid 3’, 5'-hydroxylase, naringenin 3-dioxygenase, flavonol synthase and bifunctional dihydroflavonol 4-reductase. These results provide comprehensive insights into the physiological and molecular mechanisms underlying the influence of nano-selenium on plant growth and nutritional quality. Therefore, they offer a solid theoretical basis and technical support for breeding and cultivation strategies aimed at producing selenium-rich pak choi.